The Influence of Stad Cooperative Strategies (Teaching AIDS and Multimedia Power Points) and Learning Style on Mathematics Learning Outcomes - Sufanti, Meifi; Santosa, Cecep Anwar Hadi Firdos (Universitas Tanjungpura, 2021)
This study aims to determine the effect of STAD learning strategies assisted by teaching aids and multimedia assisted PowerPoint with auditory and kinesthetic learning styles on mathematics learning outcomes. Sampling was chosen randomly (random class). This type of research used quasi-experimental with a 2x2 factorial research design. The instruments use a test of learning outcomes in the form of multiple-choice questions and a questionnaire for student learning styles. Data were analyzed using two-way ANOVA and multiple comparison tests. Based on the data analysis, it is concluded that: (1) there are differences in the mathematics learning outcomes of students in classes who receive STAD learning assisted by teaching aids between STAD learning assisted by multimedia PowerPoint (2) there are differences in learning outcomes between students with auditory and kinesthetic learning styles students with audio learning styles, student mathematics learning outcomes are not higher when taught with STAD learning assisted by PowerPoint multimedia compared to STAD learning assisted by teaching aids (4) For students with kinesthetic learning styles student mathematics learning outcomes are higher when taught with STAD learning assisted by teaching aid, compared to PowerPoint multimedia-assisted STAD learning and (5) there is an interaction between STAD learning strategies and auditory and kinesthetic learning styles. Therefore, it is concluded that with there is an interaction between learning strategies and learning styles, student learning outcomes are not only influenced by learning strategies. In this case, the STAD learning strategy assisted with teaching aids and STAD assisted with multimedia PowerPoint is not the only factor in making students understand mathematical concepts but must be based on learning styles. For auditory student learning styles, the appropriate learning strategy is to use STAD assisted by Power Point multimedia, while for students who have a kinesthetic learning style using STAD assisted by teaching aids.